Utilizing Edmodo in writing class: Why and how? - Wensi Alka (Acitya: Journal of Teaching and Education, 2020)
ABSTRACT This paper comes up to discuss the theories and previous studies about using Edmodo in writing class. Using social network system in the Industrial era 4.0 helps teaching and learning activities become more effective because students can learn in and outside the class. Thus, it is helpful especially in writing class which require long learning time to use this kind of application. Therefore, utilizing an online applications in writing class can help students to improve their writing skill and to make learning time more efficient. One of online applications that is widely used in writing is Edmodo. Generally, this paper then will discuss about explanation of writing processes, problems in writing, explanation about learning media, description of online application, description of Edmodo,benefits of Edmodo, and how to apply Edmodo in writing course. Some previous research highlighting the effect of Edmodo on student’s writing skill is the next discussion. This paper finally gives conclusion and pedagogical implication as the closing. Keywords: writing class, online application, Edmodo